FEMALE CIRCUMCISION (BETWEEN SHARIAH LEGAL EVIDENCE AND GOVERNMENT REGULATIONS) - Mundzir, Ahmad; Irfan, Moh; Setiyono, Taufiq Andre; Raharjo, Raharjo (istinbath, 2025)
The law of female circumcision in Indonesia is still a controversy between scholars, medicine, and the state. This study aims to analyze the obligation of citizens to comply with Government Regulation No. 28 of 2024, which prohibits the practice of female circumcision, from the perspective of the Shafii School, where this madhhab actually encourages it. This study uses the library research method to examine primary and secondary sources related to hadith, fiqh, madhhab Syafii, contemporary fatwa, and medical and legal aspects in Indonesia. The analysis was carried out using the approach of hadith criticism, ushul fiqh, maqashid shariah, and fiqh madhhab Syafii. The results of the study show that there is a contradiction between the classical views of the Shafii School that tend to advocate female circumcision, including the MUI fatwa, and the results of the 32nd NU Congress in Makassar. However, the principle of obedience to the government is also emphasized in this school. This study found that the sharia basis for female circumcision is dzanni, with generally weak supporting hadith and medical aspects that aggravate female circumcision that can be carried out with the support of the ushhul fiqh approach, maqashid sharia, and fiqh madhhab Syafii. In conclusion, despite differences of opinion, citizens' compliance with Government Regulation No. 28 of 2024 can be justified from the perspective of the Shafii School by considering that it does not contradict Islam. This study suggests the need to review Islamic law in fatwa institutions in Indonesia.